MASYARAKAT BELI PRODUK ROTI TERNAMA KARENA CITRA TOKO ATAU KUALITAS PELAYANAN? - Iman Sidik Nusannas (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
The study was to determine the effect of Store Image and Service Quality on Consumer Buying Interest at a famous bakery at Purwakarta. The datas taken from respondents that was questionnaired to 96 respondents with Non Probability Sampling techniques. The research method used is descriptive method which is a method that is done by collecting, presenting and analyzing data so as to provide a clear enough picture of the object under study. This study uses a multiple linear regression analysis model with the help of IBM SPSS 21 program. The results of this study indicate that the variables of Store Image and Service Quality have a positive and significant effect on Consumer Interest in a famous bakery at Purwakarta.